An Impact of Covid‐19 in Profitability of the Cooperative Organization in Khotang District - Rai, Harka Bir (DMC Journal, 2022)
The purpose of the study was to analyze the profitability ratios of co-operatives organizations in Khotang District before and after Corona virus Diseases Of 2019(COVID 19) from 2018 to 2021 A.D. To analyze the effect of profit due to Pandemic, secondary data are collected based on final audit report. In this study the quantitative research approach is used. The net profit of the two organizations is compared, the five types of the profitability ratios are calculated using formulas. The net profit ratios, Return on Shareholders’ Equity (ROSE), Return on Common Shareholders Equity (ROCSE), Return on Assets (ROA) and Return on Common Equi (ROCE) are found increased of (Subha Labha Bachat Tatha Rin Sahakari Sanstha) SLBRS whereas then other cooperative Sidda Laxmi Bachat Tatha Rin Sahakari Sanstha (SBRS) are found decreased. The ROCE of SBRS are found decreasing and decreasing then it became negative. The analysis shows that there are not any effect of Pandemic in profitability for SLBRS but another organization SBRS has adverse effect.